Effect of magnetic field on N+ Nn+ GaAs ballistic diode - Tiwari S.C. (My University, 2025)
The AC impedance of a ballistic diode under a transverse magnetic field shows distinct behaviour depending on the cyclotron frequency. An equivalent lumped parameter RLC representation is obtained. © 1985, The Institution of Electrical Engineers. All rights reserved.